Teacher beliefs about student agency in whole-class playing. (8th August 2022) - Stolp, Eveliina; Moate, Josephine; Saarikallio, Suvi; Pakarinen, Eija; Lerkkanen, Marja-Kristiina
ABSTRACT: This study explores music teachers' beliefs of student agency in whole-class playing and investigates what characterises student agency through teachers' values, actions and observations within this unique multimodal and -dimensional learning environment. Our abductive analysis of 11 interviews reveals that the role of teacher support is significant in enacting students' agency. This study provides insights into student agency through the eyes and actions of teachers within the context of whole-class playing and suggests that the enactment of different aspects of student agency is an essential feature necessary for whole-class playing to succeed.